2019
DOI: 10.3390/v11040314
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Genetics System for Cypovirus Based on a Bacmid Expressing T7 RNA Polymerase

Abstract: Dendrolimus punctatus cypovirus (DpCPV), belonging to the genus Cypovirus within the family Reoviridae, is considered the most destructive pest of pine forests worldwide. DpCPV has a genome consisting of 10 linear double-stranded RNA segments. To establish a reverse genetics system, we cloned cDNAs encoding the 10 genomic segments of DpCPV into three reverse genetics vectors in which each segment was transcribed under the control of a T7 RNA polymerase promoter and terminator tagged with a hepatitis delta viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A similar combination of cell line transfection with amplification in larvae was also used to construct a reverse genetics system for Dendrolimus punctatus cypovirus (DpCPV; Zhang et al, 2019 ). In this case, recombinant baculoviruses were employed to express T7 RNA polymerase in lepidopteran Sf9 cells which was used to drive expression of viral RNAs from co-transfected plasmids with T7 polymerase expression cassettes.…”
Section: Molecular Mechanism Of Cell Entry By Cypoviruses In Lepidopteran Insectsmentioning
confidence: 99%
“…A similar combination of cell line transfection with amplification in larvae was also used to construct a reverse genetics system for Dendrolimus punctatus cypovirus (DpCPV; Zhang et al, 2019 ). In this case, recombinant baculoviruses were employed to express T7 RNA polymerase in lepidopteran Sf9 cells which was used to drive expression of viral RNAs from co-transfected plasmids with T7 polymerase expression cassettes.…”
Section: Molecular Mechanism Of Cell Entry By Cypoviruses In Lepidopteran Insectsmentioning
confidence: 99%
“…The highest percentage of mortality was recorded by concentrate 10/100 on tobacco beetle, drugstore beetle, darkling beetle larvae, and rice weevil adults (96.67%, 96.11%, 92.78%, and 90.00%) respectively, followed by concentrate 10/500 recorded 94.44% and concentrate 10/1000 recorded 70.56 %, on tobacco beetle larvae. On the other hand, a lower percentage of mortality was recorded by concentrate 1/25000 on the adult stage of rice weevil (33.33%), (Table 2), these results were illustrated with [14][15][16].…”
Section: Effect Of (Cypovirus1) Infection On Stored Products Beetlesmentioning
confidence: 99%
“…However, sudden destruction of the central gastric tissue leads to larvae abstaining from feeding, causing a series of physiological changes accompanied by symptoms of vomiting and diarrhea. To the death of the larva after 10 days of inoculation [14][15][16]. This work was carried out to viral identity was confirmed by host range studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Daphnis nerii, it has been found that DnCPV-23 can also induce infection and death in many species of Sphingidae insects, such as Cephonodes hylas Linnaeus, Ampelophaga rubiginosa Bremer & Grey, and Agathia lycaenaria Kollar. The genome of DnCPV-23 consists of ten segments of linear double-stranded RNA, referred to as Genomic Segments 1 (S1) to 10 (S10), in accordance with the fragments from longest to shortest [7]. Our previous research and unpublished data demonstrated that the virus can successfully replicate on the Sf9 [8] and Manduca sexta cell lines QB-MS 2-2 [9].…”
Section: Introductionmentioning
confidence: 99%